Assessment of posture and foot video-computer monitoring dynamics in the implementation of physical therapy program for 5-6-year-old children with hip dysplasia consequences - Zviriaka, Oleksandr; Rudenko, Anna; Karpenko, Yulia; Demchenko, Ludmila; Kuksa, Natalia (Journal of Physical Education and Sport, 2021)
Hip dysplasia is one of the most common orthopedic pathologies, the consequences of which may be manifested by functional disorders of the musculoskeletal system in preschool age, namely: postural disorders, flat feet, valgus or varus of the lower limbs. The current algorithm and physical therapy programs are not effective enough for preschoolers with the consequences of hip dysplasia, as they do not take into account the principles of patient-centered, multidisciplinary and individually-differentiated approaches. Materials & methods: 131 children of preschool institutions were examined with the help of video-computer monitoring of the posture "Posture-2015" and the method of photometry "BIG FOOT". Results: Preliminary results of posture video monitoring showed that suboptimal statics in the sagittal plane was found out in the group of children with hip dysplasia, namely: flat-concave back - in 26 children, stooped back - in 7 children, round-concave back - in 7 children, round back - in 4 children and flat back - in 1 child. According to the videogram of foot, it was determined that the percentage of children with normal values of the angle у - without foot deformities, statistically significant (p <0.01) was higher in the comparison group in 38 children (60.3%), respectively, in the group with hip dysplasia only 14 children (20.5%) were diagnosed with a normal foot. The program of physical therapy was developed, the defining features of which are systemic and complex application of kinesiotherapy, hydrokinesiotherapy, therapeutic massage, orthopedic means and preformed physical factors. As a result of the author's rehabilitation program for children 5-6 years old with the consequences of hip dysplasia implementation, the angular parameters obtained by video monitoring in the sagittal plane, indicate an improvement in posture among children of the main group - namely reduction of thoracic kyphosis and lumbar lordosis (by angles λ1, λ2, λ3), which approached the normative values, in contrast to the results of the control group, where the dynamics was unstable. The analysis of angular and anthropomorphological indicators of the foot of children of both groups shows that the positive changes are statistically significantly more vivid in those who were engaged in the author's rehabilitation program. Discussion: Further study of this problem and generalization of scientific experience described in the literature may be a prerequisite for the formation of a clear and universal protocol for rehabilitation diagnosis, prognosis, identification of rehabilitation interventions and their evaluation in the process of eliminating the consequences of hip joint dysplasia and improving musculoskeletal function. Conclusions: The use of the developed algorithm of rehabilitation measures helped to eliminate the consequences of hip dysplasia, significantly improve the functionality of the musculoskeletal system, correct the imbalance of soft tissue components, prevent further complications, that confirms the effectiveness of the author's physical therapy program compared to the standard.